APPLICATION OF EXTRACORPOREAL TREATMENT METHODS IN THE COMPLEX THERAPY OF PATIENTS WITH CHRONIC UVEITIS (Innovate Conferences, 2025)
Uveitis represents a heterogeneous group of inflammatory diseases affecting the uveal tract and adjacent ocular structures (retina, optic nerve, vitreous body, sclera). Uveitis can be of both infectious and non-infectious origin, and although clinical manifestations may appear similar, it is essential to differentiate clinical forms due to differences in their pathophysiology and treatment strategies. Uveitis occurs when the delicate balance of the immune system is disrupted by endogenous or exogenous factors. This leads to an increase in pro-inflammatory cytokines (IL-1, IL-6, IL-12, TNF-alpha, interferons, chemokines, IL-8, and others). The action of these inflammatory mediators results in structural and functional disorganization of connective tissue and impaired microcirculation, causing hypoxia, ischemia, and various other changes in ocular tissues that contribute to disease progression.Immune disorders play a crucial role in the etiopathogenesis of uveitis. Therefore, in addition to standard therapy aimed at eliminating the pathogen, controlling inflammation, preventing synechiae formation, detoxification, and desensitization, immune correction should also be an essential part of uveitis treatment. Therapy should be pathogenetically targeted and localized to the affected tissue to maximize the efficacy-to-side-effect ratio. However, this is not always achievable, which is why the search for new methods capable of suppressing inflammatory activity and preventing immune-mediated tissue damage and vision loss with minimal side effects continues.